REFLECTIONS ON THE USE OF ANABOLIC ANDROGEN STEROIDS BY TEENAGERS INSCHOOL PHASE (Fiep Bulletin - online, 2017)
Today we are witnessing an exaggerated cult body aesthetics, through plastic surgery, aesthetic clinics is growingalong with the regulars of gyms. We cannot deny that teenagers are the main targets of media are the main consumers andfollowers of so-called "fads" and large parts of them are of school age. That is, many teenagers to join this pattern theseadolescents make use of Anabolic Androgenic Steroids (AAS). The methodology used is basic in nature, descriptive andqualitative measures. By the time, we conclude that parents, educators and teachers of physical education exert a great influenceon this young man so long to use, both for the use of these substances not modifier.
Keywords: Anabolic Steroids; Teens; School; physical education teachers